Gender Effects in Surface Electromyographic Activity of the Biceps Brachii Muscle during Prolonged Isometric Contraction - Ahamed, Nizam Uddin; Zulkifli, Md. Yusof; Alqahtani, Mahdi; Altwijri, Omar; Rahman, S. A. M. Matiur; Sundaraj, Kenneth (Elsevier, 2015)
The muscle activity, electromyographic (EMG) signal steadiness and relationships between the EMG signal and endurance time among males and females have long been investigated and continue to be a subject of controversy. The aim of this study was to explore the electromyographic effects on the biceps brachii (BB) muscle of male and female subjects during prolonged isometric contraction (for 90 s). Twenty right-handed (10 male and 10 female) subjects participated in this study. The EMG analysis was accomplished in the time domain by calculating the amplitude content of the signals as the root mean square (EMG-RMS). The statistical analysis included linear regression to examine the relationships between the EMG amplitude (%MVC) and the endurance time, repeated-measures ANOVA to assess differences among the variables, and calculation of the coefficient of variation (CoV) to assess the steadiness of the signal. The results revealed that the linear slope coefficient of the EMG as a function of time (r2 = 0.56, p < 0.05) obtained for male subjects during contraction was significantly greater than that obtained for females (r2 = 0.11, p > 0.05). Additionally, the EMG signal activity generated by the male BB muscle (10.25%) exhibits less variability than that generated by the female BB muscle (12.11%). The experimental results indicate the suitability of developing an EMG prosthetic hand controller and the use of EMG analysis in the fields of neuromuscular system research, rehabilitation engineering and movement biomechanics, which may help separate male and female subjects.